Burnout di Kalangan Pelajar Sarjana Universiti Utara Malaysia - Yazli Sufli, Mohd. Yazid (2003)
The main purpose of this study is to determine the level of burnout among Graduate students at he main campus of University of Northern Malaysia. The objectives of this study are to (1) determine the different in burnout based on selected demographic variables, (2) determine the relationships between selected demographic variables, polychronic attitude, academic goal orientation and locus of control toward the existing of burnout among the students, (3) determining the dominant factor that influence the existing of burnout among the students. The samples for this study are the Graduate students from 16 Master Programmes. A total 106 respondent were involved in this study and the finding shows that 14.2 percent was getting the burnout, 1.8 percent got the crisis of burnout and 55.7 percent has symptom of burnout. The result of the study are : (1) that there is no significant different between existing of burnout based on selected demographic variables (gender, age, marital status, number of children, type of programme study, course type, total credit hours, distant between resident to campus and occupational status) accept the variable of student status. (2) that there is no significant relationships between selected demographic variables (age, marital status, number of children, type of programme study, course type, total credit hours, distant between resident to campus and occupational status) toward the existing of burnout among the students (3) That there is no significant relationship between polychronic attitude toward the existing of burnout among the students. (4) that there is no significant relationship between academic goal orientation toward the existing of burnout among the students. (5) That there is significant relationship between locus of control toward the existing of burnout among the students. The study show that locus of control is a dominant factor that influence the existing of burnout among the students in Nothern Malaysia University. The study also has given several suggestions for the organisation to prevent the existing of burnout among the student ad several suggestions to improve the future study.